Language Attitude of Lampung Native Speakers: An Overview of Age, Gender, Educational Level, and Length of Stay - Astriawan, Deris; Ariyani, Farida; Setiyadi, Ag Bambang; Widodo, Mulyanto; Rusminto, Nurlaksana Eko (Jurnal Pendidikan Progresif, 2025)
Abstract: Language Attitude of Lampung Native Speakers:  An Overview of Age, Gender, Educational Level, and Length of Stay. Objective: The local language variety used is always related to the language attitudes that are accepted or ignored in the speech community. This study aims to describe the language attitudes held by native speakers and relate them to variables such as age, gender, education level, and length of stay. Methods: This research method uses a mixed method approach, which is a combination of quantitative and qualitative. Quantitative is used to process data sourced from instruments, while qualitative is used to reveal and describe information in the research. This research was sourced from the language attitudes of native speakers of Lampung language in Bandar Lampung City. Questionnaires were used for data collection. Findings: The results of research on language attitudes of Lampung language native speakers of 110 people who became respondents obtained 52.7% had negative language attitudes, neutral language attitudes amounted to 8.2%, positive language attitudes amounted to 34.5%, very positive language attitudes amounted to 4.5%. Conclusion: From testing the correlation of intervening variables, it was found that there was a correlation between age and language attitude. However, no correlation was found between gender and language attitude and between education level and language attitude. In addition, there is a relationship between length of stay and language attitude. Keywords: language attitudes, native speakers, lampung language.